Comparative Analysis of Rice Farming using Combine-Harvester and Thresher in Kenagarian Kambang Barat, Lengayang Sub-District, Pesisir Selatan District - Vira Desvia; Rini Hakimi; Rusyja Rustam (Universitas Andalas, 2022)
The rice harvesting process has progressed a lot. Farmers used to harvest simply using a sickle and a simple thresher machine, while nowadays, they are using the latest harvest machine, called Combine Harvester. Technological developments should enable farmers to gain more significant benefits, such as higher production, a shorter processing time for harvesting, and lower costs incurred during harvesting. This study aims to describe the characteristics of farmers who use Combine Harvester technology and farmers who use Thresher harvesting technology. This study also compares the costs of rice harvesting and production of both farmers in lowland rice farming in Kenagarian Kambang Barat, Lengayang Sub-District, Pesisir Selatan District. The farmers sampling chose as many as 30 farmers purposively for each of those using a Combine Harvester and Thresher, so the total number of farmers to be interviewed was 60. The data analysis method used in this study is the analysis of the average difference test of the independent sample Z-test model. The research finds that farmers' main reasons for using the Combine Harvester were faster harvesting times and less labor. While the main reason for farmers using the Thresher was that its cost is considered the same if using a Combine Harvester machine. Moreover, the research indicates a significant difference in the cost of harvesting and producing rice using both harvesting machines. The harvesting cost of the Combine Harvester was lower than Thresher, which was Rp. 3,543,149 and Rp. 4,385,543 respectively. The difference in harvesting cost of these two harvesting machines was Rp. 842,394. Furthermore, the rice production using the Combine Harvester is higher than the thresher harvesting machine, which was 5,312 Kg/Ha/MT and 5,089 Kg/Ha/MT, respectively, with a difference of223 kg